(11-3х)·3=15
11-3х=15:3
11-3х=5
3х=11-5
3х=6
х=6:3
х=2
(49-11х):3=9
49-11х=9·3
49-11х=27
11х=49-27
11·х=22
х=22:11
х=2
(8+х):2=42
8+х=42×2
8+х=84
х=84-8
х=76
210:7•100=3000. можешь загуглить
Пусть задуманное число x, тогда
x² = (x-1)(x-2) + 16
x² = x² - 3x + 2 + 16
3x = 18
x = 6
Ответ: 6
1цел 3/7 z=1цел 3/8-7/8=11/8-7/8=4/8, 1цел 3/7=4/8=1/2, z=1/2 : 1цел3/7=1/2 :10/7=1/2 х 7/10=7/20, z=7/20.
(8/15 + 2/9 y)=2 х 3/5=6/5, 8/15 + 2/9 y=6/5, 2/9 y=6/5 - 8/15=18/15 -8/15=7/15, 2/9y=7/15, y=7/15 : 2/9=7/15 х 9/2=63/30=21/10=2цел 1/10, z=2цел 1/10